Determination of biokinetic coefficients of an aerobic system for potato starch removal - Yudy Andrea Londoño-Cañas (Ingeniería y Competitividad, 2023)
This study presents the performance of a laboratory scale completely mixed aerobic reactor for starch wastewater treatment. The reactor was operated for 119 days, divided into 5 operational phases which included the start-up and the variation of cell-residence time. In order to determine the biokinetic coefficients for starch removal, the cell-residence time was varied between 20 to 4 days, and the system operation was set to a hydraulic retention time of 24 hours with a completely mixed reactor setup. The chemical oxygen demand concentration was 1000mg/L in the inflow of the reactor and dissolved oxygen remained above 2mg/L.In this experimentation time, the parameters such as pH, chemical oxygen demand (in the influent and effluent), dissolved oxygen and mixed liquor suspended solids were monitored. The calculation of biokinetic constants was done by an approximate method, using the graphical Lineweaver-Burk method. The biokinetic coefficients determined were for maximum substrate removal rate (0), half saturation rate constant or affinity constant (), sludge yield coefficient (Y), and microbial decay or indigenous respiration rate (). The results showed that Y, (0), and (), were in the range of 0.3- 0.7 mgSSV/mgBOD5, 2- 8 day1 and 40-120 mg/L (COD- BOD5), respectively. Values of the coefficients were within the range of those reported for conventional activated sludge processes.